Determining the degree of unevenness in the working cycle of an internal combustion engine when operating on different types of fuel - Mytrofanov, Oleksandr; Proskurin, Arkadii (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the degree of non-uniformity in the working cycle of an internal combustion engine with spark ignition when using different types of fuel. The task addressed relates to the lack of comprehensive experimental studies that take into account the influence of the type of fuel, the composition of the fuel-air mixture, and the statistical characteristics of the working cycle parameters based on a large array of indicator diagrams. This work reports experimental indicator diagrams of partial engine operating modes when using gasoline, propane-butane, and synthesis gas with a hydrogen content of 43%. It was established that normal engine operation on synthesis gas is ensured at an excess air coefficient of 1.35…1.75. The correspondence of the distribution of maximum combustion pressure to the normal law according to the χ2 criterion has been confirmed. It was shown that the presence of hydrogen in the composition of synthesis gas significantly reduced the degree of non-uniformity of the working cycle of the spark ignition engine. It was found that the minimum value of the degree of unevenness of the working cycle is observed within the range of the excess air coefficient of 1.05...1.25. As the mixture is depleted, a gradual increase in the degree of unevenness of the working cycle is observed. When α ≈ 2 is reached, the unevenness of the working cycle on synthesis gas reaches the minimum value of unevenness when the engine is operating on gasoline at α = 0.9...1.0. A feature of the results is the combination of an experimental approach with a statistical analysis of a large sample of indicator diagrams, which made it possible to reliably estimate the degree of unevenness and establish the optimal ranges of the excess air coefficient for different fuels. The results could be used in optimizing the working processes of spark-ignition engines, designing mixture control systems, as well as in using alternative fuels, in particular synthesis gas, under partial load conditions